Estimates of the Abundance of Cetaceans in the Central North Atlantic from the T-NASS Icelandic and Faroese Ship Surveys Conducted in 2007 - Pike, Daniel G.; Gunnlaugsson, Thorvaldur; Mikkelsen, Bjarni; Halldórsson, Sverrir Daniel; Víkingsson, Gísli; Acquarone, Mario; Desportes, Geneviève (NAMMCO Scientific Publications, 2020)
The Trans-North Atlantic Sightings Survey (T-NASS) carried out in June-July 2007 was the fifth in a series of large-scale cetacean surveys conducted previously in 1987, 1989, 1995 and 2001. The core survey area covered an area of about 1.8 million nm² spanning from the Eastern Barents Sea at 34°E to the east coast of Canada, and between 52°N and 78°N in the east and south to 42°N in the west. We present design-based abundance estimates from the Faroese and Icelandic vessel survey components of T-NASS, as well as results from ancillary vessels which covered adjoining areas. The 4 dedicated survey vessels used a Buckland-Turnock (B-T) mode with a tracker platform searching an area ahead of the primary platform and tracking sightings to provide data for bias correction. Both uncorrected estimates, using the combined non-duplicate sightings from both platforms, and mark-recapture estimates, correcting estimates from the primary platform for bias due to perception and availability, are presented for those species with a sufficient number of sightings. Corrected estimates for the core survey area are as follows: fin whales (Balaenoptera physalus): 30,777 (CV=0.19); humpback whales (Megaptera novaeangliae): 18,105 (CV=0.43); sperm whales (Physeter macrocephalus): 12,268 (CV=0.33); long-finned pilot whales (Globicephala melas): 87,417 (CV=0.38); white-beaked dolphins (Lagenorhynchus albirostris): 91,277 (CV=0.53); and white-sided dolphins (L. acutus): 81,008 (CV=0.54). Uncorrected estimates only were possible for common minke whales (B. acutorstrata): 12,427 (CV=0.27); and sei whales (B. borealis): 5,159 (CV=0.47). Sighting rates from the ancillary vessels, which used a single platform, were lower than those from the dedicated vessels in areas where they overlapped. No evidence of responsive movement by any species was detected, but there was some indication that distance measurements by the primary platform may have been negatively biased. The significance of this for the abundance estimates is discussed. The relative ...